QOLP-06. BODY IMAGE DISTURBANCE IN PATIENTS WITH PRIMARY BRAIN TUMORS. (5th November 2018) - Rowe, Lindsay; Vera, Elizabeth; Acquaye, Alvina; Crandon, Sonja; Fletcher Ruiz, María; Aboud, Orwa; Boris, Lisa; Brown, Miranda; Garren, Nancy; Ji, Ming; Levine, Jason; Mackey, Megan; et al.
Abstract: BACKGROUND: Perception of body image is an important issue for cancer patients, as patients with body image concerns are susceptible to psychosocial consequences such as depression, anxiety, difficulty coping, and poor quality of life (QoL). While this concern has been documented in patients with similar heightened risk due to visible disfigurement and lifestyle alterations, such as in head and neck tumors, currently no data exists of this QoL issue in patients with primary brain tumors (PBT). METHODS: A cross-sectional survey of 100 PBT patients was conducted as part of an IRB approved prospective protocol using structured questionnaires. Participants completed the 10-item Body Image Scale (BIS) questionnaire to assess the prevalence of body image disturbance. Clinically significant body image disturbance was defined as a BIS score ≥ 10. Cronbach's alpha was used to assess reliability. RESULTS: The median age was 48 (range 23–74), 86% were Caucasian, and 56% were male. Glioblastoma was the most common diagnosis (32%), with low grade tumors (I-II) representing 30% of the sample. Median time from initial diagnosis was 5 years (range 0–22), and 64% of patients had a KPS of ≥ 90. Overall, the median BIS score was 5 (range 0–27). The prevalence of clinically significant body image disturbance was 28% (95%CI: 19%-37%). Cronbach's alpha for the BIS in this population was 0.91, with all 10 items contributing to its reliability. CONCLUSIONS: This is the first study to explore altered body image in PBT patients. Clinically significant body image disturbance was present in nearly 1/3 of patients, and was similar to other solid tumor patients felt to be at heightened risk. The BIS demonstrated good internal consistency. This data supports future research into the characteristics and etiology of this QoL issue among PBT patients.